Early Plasmodium‐induced inflammation does not accelerate aging in mice. (17th October 2018) - Lippens, Cédric; Guivier, Emmanuel; Reece, Sarah E.; O'Donnell, Aidan J.; Cornet, Stéphane; Faivre, Bruno; Sorci, Gabriele
Abstract: Aging is associated with a decline of performance leading to reduced reproductive output and survival. While the antagonistic pleiotropy theory of aging has attracted considerable attention, the molecular/physiological functions underlying the early‐life benefits/late‐life costs paradigm remain elusive. We tested the hypothesis that while early activation of the inflammatory response confers benefits in terms of protection against infection, it also incurs costs in terms of reduced reproductive output at old age and shortened longevity. We infected mice with the malaria parasite Plasmodium yoelii and increased the inflammatory response using an anti‐IL‐10 receptor antibody treatment. We quantified the benefits and costs of the inflammatory response during the acute phase of the infection and at old age. In agreement with the antagonistic pleiotropy hypothesis, the inflammatory response provided an early‐life benefit, since infected mice that were treated with anti‐IL‐10 receptor antibodies had reduced parasite density and anemia. However, at old age, mice in all treatment groups had similar levels of C‐reactive protein, reproductive output, survival rate, and lifespan. Overall, our results do not support the hypothesis that the benefits of a robust response to malaria infection in early life incur longer term fitness costs.